MODEL SELF-DISCLOSURE GENERASI Z PENGGUNA BERAT MEDIA SOSIAL - Sari, Wulan Purnama; Irena, Lydia (Interaksi: Jurnal Ilmu Komunikasi, 2023)
Based on the results of previous research, it was found that Instagram, Twitter, TikTok, YouTube, Discord, and also Facebook became the social media most often used by Generation Z as heavy users of social media in conducting self-disclosure. Self-disclosure is divided into negative and positive, positive things become open areas that are shared and can be known by many people, while negative things are the opposite. Generation Z as heavy users of social media conduct self-disclosure about various personal information accurately and honestly through social media, this is done consciously with the aim of building relationships with other people. Therefore, this study was conducted with the aim of describing and analyzing the self-disclosure model of Generation Z heavy users on social media. The research method uses a qualitative approach with phenomenological methods. Data collection was carried out using focus group discussion techniques, with the selection of resource persons based on pre-determined criteria. The results showed that the self-disclosure model of generation Z who became heavy users of social media had the largest proportion in terms of valence, intimacy, and intention.